"Geo-Political Economy" and Ecosystem in Asian I&CT Markets - Takahiro Kawamata (International Telecommunications Society (ITS), 2018)
Since the East Asian Miracle report was published by the World Bank in 1993, East Asian countries have achieved economic development with the "flying geese pattern" respectively as well as advancements in informatization based on each political and cultural context. In particular, the revolution in information and communications technology (I&CT) drives commercial and social usage of the Internet throughout multiple devices such as personal computers, tablets, and smart-phones. East Asian cultural contexts thereby create commonalities over their territories and maintain their distinctive characters as well. While telecommunications and media industries are under governmental control, with government regulations in most Asian countries, platform businesses such as social network services (SNSs), have expanded across borders, demonstrating the principle of network externality and economy. In addition, cultural and/or social contents easily expand with identity and universality as high culture and with popularity as pop- and/or sub-cultures among younger generations within areas. This paper examines the potential of East and South East Asian markets including not only China, Korea, and Japan, but also Taiwan, Hong Kong, and Singapore, for mobile and wired communications, their technologies, services, content, and applications. It also describes the dynamism of networking among interested players over the next generation of information and communication technologies and their applications, such as SNSs and "FinTech", including mobile payment and e-commerce, as well as content including audio and visual content, and game software; in the context of the "Ecosystem" of I&CT business and the path-dependency of social shaping of technological trajectories as enhanced in each political and cultural territory. There may be a dramatic change occurring in the structure of the industry affecting not only telecommunications network components, terminal equipment vendors and software developers, but also network operators and service providers located in Asian territories. Therefore, our analysis places emphasis on the dynamic formulation of multi-tiered and multifaceted frameworks of "Geo-Cultural Informatics," which encapsulates the geo-politics and geo-economics associated with cultural informatics, within industrial clusters over Asian marketplaces. This paper also suggests a new framework of market structure with some hieratic layers and geographic areas, e.g. living area (space) 「生活圏」, commercial area (sphere)「商業圏」, economic zone (block)「経済圏」. These areas/spheres are composed with cultural and political inherence based on geography and history respectively as well as path-dependency on technological and institutional trajectory. Especially electronic commerce (e-commerce), which is not only the trade of digital contents and services, but also online shopping with digital payment/settlement, e.g. electronic money and credit card authorization including PayPal, reflects cultural contexts and/or political institutional frameworks, even if the compatibility and settlement system between nations has been ensured. In the e-commerce facilitated by FinTech, it can be seen the battles and/or alliances between Internet service providers, e.g. Amazon.com (US), Alibaba (CN), Tencecnt (CN), Kakao Talk (KR), LINE (JP), Facebook (US), Twitter (US), Instagram (US), and local providers, and financial providers, including credit card companies, banks, insurance and securities companies, for customer's accounts and records of their preferences and assets. We finally discuss on the geo-political economic issues of the digital economy in Asian living/commercial/economic areas/spheres within the ecosystem of ICT.
Keywords: 330; Evolution of Technology; Ecosystem of industries; Geo-politics; Geo-economics; "Geo-cultural informatics"